Reisen und Gärten Reisen, Reiseberichte und Gärten vom Mittelalter bis in die Gegenwart - Fischer, Hubertus; Wolschke-Bulmahn, Joachim (CGL-Studies, 2020)
With volume 26 of the CGL-Studies, the Center for Garden Art and Landscape Architecture (CGL) of Leibniz Universität Hannover continues after volume 11 (H. Fischer, S. Thielking, J. Wolschke-Bulmahn, eds, Reisen in Parks und Gärten. Umrisse einer Rezeptions- und Imaginationsgeschichte), and volume 23 (Hubertus Fischer, Georg Ruppelt, Joachim Wolschke-Bulmahn, eds, Eine Reise in die Schweiz. Das Reisetagebuch des hannoverschen Hofgärtners Heinrich Ludolph Wendland aus dem Jahr 1820) continues the scholarly examination of historical travelogues in their content of information on the history of gardens and travel as well as on historical aspects of landscape perception. Volume 26 presents the results of the symposium held in February 2016 and funded by the Volkswagen Foundation, ""Travel and Gardens. Travel, Travelogues, and Gardens from the Middle Ages to the Present."" The individual chapters are dedicated to topics such as travel literature and garden history, travelogues in garden art and garden monument preservation, travel, nature and landscapes, or travelogues in their significance for the history of the horticultural profession. Horticulture and landscape architecture in modern travel as well as editorial aspects of travelogues are further thematic foci of the volume.